Controle De Plantas Daninhas Com Herbicida Glyphosate Utilizando Diferentes Pontas De Pulverização - De Castro Barros, Murilo Peres (2014)
This work aimend to evaluate the affect of different spray associated with different doses of glyphosate in control weeds dried for Summer planting. The experimental design was a randomized block design with thirteen treatments and four replications. The doses of glyphosate were 480, 720 and 960 g i.a. ha-1. The nozzles used were: type range-XR; type range air induction-AI; pre-orifice type TT; and type double fan TJ. The experiment was conducted in the field experimental UEMS, Unit Cassilandia during twenty-eight days with ratings of control at 7, 14, 21 and 28 days after application. A selection of spray nozzles in the use of graut glyphosate was performed by assessing the weed control of area. Aside from the type of XR, the other ends AI TT, and TJ, showed better weed control until 21 DAA. However, at 28 DAA the AI did not differ from the XR evaluations of weed control. Doses of ghyphosate more efficient for the weed control were higher than 720 g i.a. ha-1.